2019
DOI: 10.26719/emhj.18.070
|View full text |Cite
|
Sign up to set email alerts
|

Influenza pandemic preparedness in the World Health Organization Eastern Mediterranean Region

Abstract: Background: Preparedness is key to controlling influenza pandemics and epidemics. Aims: A comprehensive literature review was conducted to analyse the response and preparedness to influenza pandemics in the World Health Organization Eastern Mediterranean Region (WHO/EMR). Methods: Published and grey literatures were searched in PubMed, Scopus, and Google scholar, and the WHO/EMR online databases. International and national plans were searched via official websites of the relevant ministries of the countries. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…The Middle East has been experiencing an increase in several countries in the number of positive cases where the health-care infrastructure is lagging (Khan et al, 2019). On an economic level, while the COVID-19 pandemic is having an acute effect globally, the Middle East is said to be especially impacted due to the sharp drop in oil prices and the dramatic decrease in religious tourism (Egel et al, 2020;Ng, 2020).…”
Section: Literature Review 21 Middle Eastern Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…The Middle East has been experiencing an increase in several countries in the number of positive cases where the health-care infrastructure is lagging (Khan et al, 2019). On an economic level, while the COVID-19 pandemic is having an acute effect globally, the Middle East is said to be especially impacted due to the sharp drop in oil prices and the dramatic decrease in religious tourism (Egel et al, 2020;Ng, 2020).…”
Section: Literature Review 21 Middle Eastern Contextmentioning
confidence: 99%
“…Ultimately, the economy worldwide is facing a challenge. The Middle East has been experiencing an increase in several countries in the number of positive cases where the health-care infrastructure is lagging (Khan et al. , 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The Middle East witnessed a rapid rise in the number of confirmed cases with Iran emerging as its epicenter. This outbreak comes as yet another striking reminder that the preparedness of Middle Eastern countries' healthcare systems for emerging global infectious diseases is still lagging (11). In addition, there have been no clear strategies or plans shared by countries in the region to suggest a coordinated response.…”
mentioning
confidence: 99%
“…The region is also located amidst four of the eight global migratory bird flight paths, making it a hot spot for zoonotic transmission of avian influenza viruses [ 7 ]. Furthermore, studies have shown that the EMR countries’ preparedness for possible pandemics or epidemics is variable and generally lagging and research on the subject is limited [ 7 , 8 ]. This was obvious throughout the COVID-19 pandemic by illustrating the importance of a more significant commitment to research on pandemic preparedness [ 9 ].…”
Section: Introductionmentioning
confidence: 99%